Emerging trends in applications and infrastructures for computational biology, bioinformatics, and systems biology : systems and applications - Tran, Quoc-Nam; Arabnia, Hamid (Cambridge, MA : Morgan Kaufmann/Elsevier Ltd., 2016)
"Emerging Trends in Computational Biology, Bioinformatics, and Systems Biology discusses the latest developments in all aspects of computational biology, bioinformatics, and systems biology and the application of data-analytics and algorithms, mathematical modeling, and simu- lation techniques"--
Chapter 5:Comparison Between OpenMP and Mpich Optimized Parallel Implementations of a Cellular Automaton that Simulates th ...5.1. Introduction; 5.1.1. The Cellular Automaton Game of Life; 5.2. MPICH Optimized Approach of the Cellular Automaton; 5.2.1. MPI Standard; 5.2.2. Description of the MPICH Approach of the Cellular Automaton; 5.2.3. MPICH Implementation of the Cellular Automaton; Code 1. Program code of the MPICH version of Game of Life; 5.3. OpenMP Optimized Approach of the Cellular Automaton; 5.3.1. Open Multiprocessing.
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Computational biology; Bioinformatics; Systems biology; Computer science; Big data; NATURE / Reference; SCIENCE / Life Sciences / Biology; SCIENCE / Life Sciences / General; COMPUTERS / Bioinformatics; Big data; Bioinformatics; Computational biology; Computer science; Systems biology; Electronic books; Electronic books